2000
DOI: 10.1046/j.1523-5394.2000.81012.x
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Patient Perspectives on Colorectal Cancer

Abstract: These data indicate that patient information needs to be provided in the most common terms and the most straightforward language. Information also may need to be repeated and should include attention to long-term management of the illness. Health professionals should assume that patients may have difficulty in illness management and should encourage a discussion of patients' concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
98
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 25 publications
8
98
2
Order By: Relevance
“…1,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Two further studies that were only published as conference abstracts were identified, and are not discussed further due to the limited information presented. 36,37 Two projects on the National Research Register were identified, for which no results were available.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…1,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Two further studies that were only published as conference abstracts were identified, and are not discussed further due to the limited information presented. 36,37 Two projects on the National Research Register were identified, for which no results were available.…”
Section: )mentioning
confidence: 99%
“…28,29 A summary of included studies is presented in Table 1. Ten studies evaluated breast cancer followup, 1,19,20,22,24,26,[28][29][30]32 four multiple cancer sites, 21,27,34,35 two colorectal, 12,33 two lung, 25,31 and one study evaluated gynaecological cancers. 23 Eight studies examined the views of healthcare professionals, 1,21,[25][26][27]30,31,35 four of which examined the views of GPs.…”
Section: )mentioning
confidence: 99%
“…Qualitative studies have helped to explore various aspects of individuals' experiences of colorectal cancer such as the psychosocial impact and quality of life (Dunn et al, 2005;Ramfelt et al, 2002;Sahay et al, 2001), adjustment to diagnosis and treatment (Hubbard et al, 2010;Taylor et al, 2001Taylor et al, , 2010 including an ostomy or stoma (McMullen et al, 2008(McMullen et al, , 2014, and healthcare needs or preferences (Beaver et al, 2010;McCaughan et al, 2011McCaughan et al, , 2012Rozmovits et al, 2004). Some studies have included partners or other relatives, describing issues such as their information needs (Broughton et al, 2004), the impact of treatment (Emslie et al, 2009;Ohlsson-Nevo et al, 2011, caregiving and daily life (Houldin, 2007;Sjovall et al, 2011), along with the economic and emotional consequences (Céilleachair et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Survivors of colorectal cancer are known to have specific information and support needs that are not met through traditional hospital follow-up (Nikoletti et al, 2008;Rozmovits et al, 2004;Sahay et al, 2000). The UK's National Cancer Survivorship Initiative (NCSI) calls for radical changes to the way follow-up/aftercare is provided following treatment, with a focus on providing patients with the information they need to live well beyond diagnosis, promoting supported self-management and evaluating alternative models of follow-up care (Department of Health, 2010).…”
Section: Introductionmentioning
confidence: 99%